BULLYING DI DALAM DUNIA PENDIDIKAN: PERSPEKTIF SOSIOLOGI PENDIDIKAN DAN RESIKO KEMATIAN SISWA - Adinda Putri Maharani (Yayasan Literasi Sains Indonesia, 2024)
The purpose of this arrangement is to analyze how the perspective of the sociology of education responds to the phenomenon of bullying that often occurs in the world of education which can eventually cause the risk of death for its victims. The method used to explore related to this case is a literature study, which involves collecting information from various written sources, such as books, articles, and related documents. The results show that in the world of education, bullying behavior is an aggressive act, both physically and verbally, carried out by individuals repeatedly against other individuals that often occurs in the scope of the educational environment and adversely affects the victim, Both stress, depression, academic decline, to the risk of death. Bullying behavior can be seen as a result of the social structure in the school environment, where the presence of unwritten social hierarchies causes some children who are considered more popular or have power more likely to exhibit this behavior. The reason behind such behavior is to maintain or improve their social status in the hierarchy. So in this case it needs to be seen where the role of teachers is to overcome this problem, especially to minimize the effects that will be caused to victims.